Penghayatan Sakramen Perkawinan Pasangan Suami-Istri Katolik Membuahkan Keselamatan - Theresia Vita Prodeita (Jurnal Teologi (Journal of Theology), 2019)
The Church has a doctrine of marriage authentic values. Church regards marriage as a supreme and sacred life call because God himself leads and blesses this marriage institution. The sacrament of marriage itself does not spare from the influence of globalization which cause the increasing of civil divorce cases. Nevertheless there are still a lot of catholic spouses who are able to maintain their fidelity in marriage. Based on this background, the author conducted a field study of the Catholic spouses who are active in the church activities and who provide a good commitment to their marriage. The method of research is a mixed method. As a researcher, the author conducted a questionnaire to get the quantitative data and an in-depth interviews with selected spouses as respondents. After collecting data, the author makes an analysis of the data, an executive summary, a conclusion of the study, and pastoral recommendations.Finally, the author concludes that the nobleness of marriage dignity actually is conducted by the couple of husband and wife. The family pastoral care efforts need to be developed and given serious concern in parish. One of the important pastoral efforts to be implemented is ranging marriage catechesis for children, teenagers, and adults.